My Apparel / Fazlinur Mustaqim Hussain … [et al.] - Hussain, Fazlinur Mustaqim; Mohamad Wan, Norsuhada; Mohamad, Asrul Hairi; Jibril, Nur Hazwani (2006)
There is still room for one more business of producing uniforms around Petaling Jaya, specifically for hotel's and restaurant's use. So far there are more non-Bumiputera owned businesses in the field, but with intense research and careful planning, we are confident that we still have the competitive edge in getting the attention and share of market. Our company is named as MyApparel and it will be commence in 1st January 2OO7. We decided to have our establishment placed in Petaling Jaya district because we found that there is a large market for uniforms in this area. There are plenty of hotels and restaurants erected and the combined workforce who requires uniform is pretty big, totaling around RM 7.8 million in sales estimated by considering that each worker will have to have three uniforms of the same kind. MyApparel is run by four different departments, which are Administration, Marketing, Operation and Finance. These departments are leaded by each of the shareholders, and they all play a big part in executing our plan smoothly and achieve our organization's goals. Our company is a manufacturing company, which means that we have to carefully plan so that our sales will be enough to covering the enormous operation costs. By achieving this, we used a mixed strategy of setting the price, which are value-based pricing and the usual cost-based pricing. Even though we have only three competitors whom we think are almost in the same league as us, we expect tough competition from all three of them. Therefore, there is no room for mistakes in our planning, and we also have to be very alert in any changes in the business climate.